Exploring the philosophical engagements for community economic development analytical framework for poverty alleviation in South African rural areas - EA Ndaguba; Barry Hanyane (Cogent Economics & Finance, 2018)
This paper is the second paper in a series of papers on Community Economic Development Strategic Framework for Poverty Alleviation in Local Government with particular attention to the Raymond Mhlaba Local Municipality (RMLM). The objective of this paper is twofold: (i) to examine the rationale for community economic development in contemporary philosophy for poverty reduction and (ii) to develop an analytical framework for community economic development for alleviating poverty. It uses existing statistics and research data from Statistics South Africa and other indexes cushioned with over 100 research papers to generate data for this argument. Theme and narrative analysis were used to analyse the data for this paper. In conclusion, the paper demonstrated that for poverty to be alleviated-local investments, buying locally made products, patronising local shops and spaza shops, local regeneration, local reconversion, community linking, and building sustainable capital and market in communities are integral for the survival of any community that intends to be economical viable or sustainable. It recommends that one of the ways in which community viability or sustainability may be guaranteed is through regeneration/reconversion policy and a framework that articulates and harmonise sustainability issues and localisation challenges of communities in each locality.
Keywords: 330; Community development; community economic development; economic development; localism; poverty alleviation; social justice; social transformation; sustainable development